Pembuatan Minuman Sehat Instan Kering Dari Sari Jahe - Andilala; Muhammad Bagas Fahriansyah; Juliana Sion Sihombing; Aryeshi Putri; Dinda Ilyasa Fatihah; Juliantika; Muhammad Nizam Nawawi; Winda Wardani Wijaya (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The Community Service Program (PKM) in Bingkat Village, Pegajahan District, Serdang Bedagai Regency, aims to improve community welfare by making instant dry healthy drinks from ginger extract. This activity involves lecturers and students from the Indah Medan Health Sciences College, with a focus on empowering housewives who are members of the PKK group. The training was attended by around 60 participants, who showed active participation during the discussion session on the benefits of ginger and the process of making healthy drinks. The training method includes lectures and practices, participants learn about the properties of ginger, how to choose quality ingredients, and packaging techniques. After the training, participants succeeded in producing instant dry healthy drinks, which are considered to have a distinctive aroma and fresh taste. A marketing plan was also prepared, including identifying target markets and promotional strategies through social media. This program has a positive impact on the family economy, increasing income through product sales. The community is expected to be able to increase their immune system and reduce the risk of disease by consuming this product regularly. The sustainability of the program is very important, so support is needed from the village government and related institutions for further development. Challenges faced include limited access to markets and capital, which require solutions through microfinance and effective marketing strategies.